2014
DOI: 10.1007/s00414-014-0978-0
|View full text |Cite
|
Sign up to set email alerts
|

Sodium/proton exchanger 3 (NHE3) and sudden infant death syndrome (SIDS)

Abstract: The sodium/proton exchanger protein 3 (NHE3) is located in chemosensitive areas of the medulla oblongata and plays an important role in the central control of respiration. Overexpression of NHE3 is correlated with lower respiration and might therefore contribute to the vulnerability of infants dying suddenly and unexpected (sudden infant death syndrome, SIDS). Our aim in this study was to verify already reported genetic variations in the NHE3 gene in an independent SIDS cohort from Switzerland. Two single nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Most comparable studies have a cohort size of well under 200 [e.g., [31][32][33], and recently, it was proposed that such a study should ideally comprise at least 200 case samples [34]. This criterion would be almost doubly fulfilled by our study on 366 SIDS cases and 421 controls.…”
Section: Discussionmentioning
confidence: 91%
“…Most comparable studies have a cohort size of well under 200 [e.g., [31][32][33], and recently, it was proposed that such a study should ideally comprise at least 200 case samples [34]. This criterion would be almost doubly fulfilled by our study on 366 SIDS cases and 421 controls.…”
Section: Discussionmentioning
confidence: 91%
“…Three SNPs (rs71597645 (G1131A), rs2247114 (C2405T), and rs187829972 (C1197T)) that may explain the overexpression of NHE3 were reported to be associated with SIDS [ 7 ]. However, conflicting results showing a lack of association of these three variants with SIDS were reported in a validation study [ 8 ]. In our study, no significant association of rs71597645 with SIDS was observed, even after meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the same research group identified three single-nucleotide polymorphisms (SNPs) from NHE3 (missense variant: C2405T; promoter variants: G1131A and C1197T) that were significantly associated with SIDS [ 7 ] and might explain the previously reported overexpression of NHE3 in the brainstem. However, a subsequent study failed to confirm these results [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…ClC5, FcRn, NaPi-IIa gene are related with metabolic renal disease. DAB2, GIPC has an uncertain meaning in human pathology, but their pathogenic effect must be explored [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].Considering the interaction between these genes, it would be very useful to analyze the relationship between polymorphisms of single base changes (SNP) of these genes, or the blocks of haplotypes and haplogroups that can be constructed with sets of SNP in T2D patients. Specially, the relationship of such variants with the development of peripheral neuropathy and the appropriate metformin doses.…”
mentioning
confidence: 99%
“…ClC5, FcRn, NaPi-IIa gene are related with metabolic renal disease. DAB2, GIPC has an uncertain meaning in human pathology, but their pathogenic effect must be explored [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%